Apotransferrin induces cAMP/CREB pathway and cell cycle exit in immature oligodendroglial cells - Garcia, Corina Ileana (2004)
We have demonstrated previously that a single intracranial injection of apotransferrin (aTf) in neonatal rats increases myelination and accelerates differentiation of oligodendroglial cells (OLGc). In addition, we have shown through in vitro experiments that OLGc isolated from 4-day-old rats (OLGc-4) treated with aTf were more differentiated than were controls although aTf had no effect upon OLGc isolated from 10-day-old animals (OLGc-10). In the present work, we analyzed the role of second messengers in the effect of aTf upon the maturation of OLGc at different stages of development. We isolated OLGc-4 and OLGc-10 from rat brain using a Percoll density gradient and briefly treated the cells with a pulse of aTf or kept them in culture during 2 days in the presence or absence of aTf. In OLGc-4, after a short pulse of aTf, there was an increase in the levels of cyclic AMP (cAMP), in the phosphorylation of cAMP response element-binding protein (CREB) and in the DNA-binding capacity of cAMP-responsive transcription factors. Treatment of OLGc-4 with aTf diminished bromodeoxyuridine (BrdU) incorporation and changed levels of p27 and cyclin D1. This glycoprotein seemed to act on OLGc through the cAMP pathway only at early stages of development and on a certain sensitive cell population, accelerating their differentiation, probably as a consequence of premature withdrawal from the cell cycle.